2011
DOI: 10.4103/0975-5950.94470
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice regarding risk of HIV infection through accidental needlestick injuries among dental students of Raichur, India

Abstract: Background:Injuries from occupational accidents are associ-ated with agents of biological risk, as they are the gateway to serious and potentially lethal infectious diseases that can be spread by contact between people. Several studies have demonstrated that dental students are among the most vulnerable to blood-borne exposure.Objectives:To assess the knowledge, attitude and practice regarding risk of HIV transmission through accidental needlestick injury amongst dental students and providing supportive and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 8 publications
5
18
2
1
Order By: Relevance
“…However, the more advanced semesters, as might be presumed, showed better risk perception than those less advanced, as students in the latter stages are just beginning to form their perceptions of risk. The same result has been described in other studies 2,[9][10][11][14][15][21][22] . In contrast, research performed by Jafari et al 23 demonstrated that students in the final years of an Iranian university's dentistry course showed good risk perception regarding the prevention and transmission of HIV due to their constant contact with sick patients, since these students helped out in a care center for patients with diseases.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, the more advanced semesters, as might be presumed, showed better risk perception than those less advanced, as students in the latter stages are just beginning to form their perceptions of risk. The same result has been described in other studies 2,[9][10][11][14][15][21][22] . In contrast, research performed by Jafari et al 23 demonstrated that students in the final years of an Iranian university's dentistry course showed good risk perception regarding the prevention and transmission of HIV due to their constant contact with sick patients, since these students helped out in a care center for patients with diseases.…”
Section: Discussionsupporting
confidence: 80%
“…As for post-accident measures, it may be inferred from this study that students have not been properly instructed or do not seek to apply the knowledge they have acquired, as only 12% filled in the biological accident notification forms and only 16% asked for the source-patient's serology. Other studies in the literature also revealed poor adherence to postexposure protocols and unsatisfactory knowledge in this regard 2,9,10,[21][22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to dispose the sharps properly, otherwise they might get entangled in linen or garbage and can injure the health workers who encounter them unexpectedly [4]. In spite of published literature and training programmes to prevent these injuries, significant success has not been achieved in preventing needle stick injuries.…”
Section: Introductionmentioning
confidence: 98%
“…[1] Guruprasad and Chauhan reported that “There is a need of correcting the existing misconceptions through education programs early in the course and providing supportive and proper guidelines regarding needlestick injuries and HIV infection”. [1] Indeed, the concern on medical personnel accidental exposure and HIV infection risk has been talked for a long time. It is no doubt that the students are the most vulnerable group with the highest risk due to their lowest experience and knowledge.…”
mentioning
confidence: 99%